1998
DOI: 10.3354/meps167291
|View full text |Cite
|
Sign up to set email alerts
|

Particulate dimethyl sulphoxide in seawater:production by microplankton

Abstract: Dirnethyl sulphoxide (DMSO) represents a major pool of dissolved dimethylated sulphur in seawater However, the origin and fate of this compound in the marine environment, and its role in the biogeochermcal cycle of dimethyl sulphide (DMS), remain unclear. The only established route for the formation of DMSO in oxygenated seawater is photochemical oxidation of DMS. It is not known whether significant biotic production pathways exist. In a study of methylated sulphur speciation in coastal North Sea waters and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 18 publications
9
79
2
Order By: Relevance
“…It is possible, albeit unlikely, that sources produce DMSO in high enough local concentrations that it could exist in the solid state. A more likely scenario is that DMSO could exist in pseudoparticulate form by adsorbing to the silicate and calcite surfaces of marine diatoms and coccolithophorids, given its strong capacity to adsorb to positively charged surface (7,16). Finally, cold temperatures may inhibit diffusion of DMSO into the cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible, albeit unlikely, that sources produce DMSO in high enough local concentrations that it could exist in the solid state. A more likely scenario is that DMSO could exist in pseudoparticulate form by adsorbing to the silicate and calcite surfaces of marine diatoms and coccolithophorids, given its strong capacity to adsorb to positively charged surface (7,16). Finally, cold temperatures may inhibit diffusion of DMSO into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible advantage may be to optimize substrate utilization. For example, algae and other eukaryotic microplankton are known to produce DMSO in aquatic environments (6,7), and strains of Shewanella have been isolated from the surface of algae (35,36). If positioning the DMSO reductase externally allows Shewanella to more efficiently capture DMSO, Shewanella might have a selective advantage for using this substrate over other organisms with an internal DMSO reductase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, DMSPd is very low compared to DMSPp while DMSOd dominates DMSO pool and can exceed concentration of both DMS and DMSPd in euphotic waters (Hatton and Wilson, 2007). Simó et al (1998) reported DMSOp and DMSOd concentrations for North Sea samples containing Phaeocystis (UK coast, in June) of respectively 16 and 25 nmol L − 1 . This is lower than our concentrations but their samples were probably taken at the end of Phaeocystis bloom, while our samples covered the whole bloom period.…”
Section: Seasonal Evolution Of Chl-a and Dms(po) Concentrationmentioning
confidence: 99%
“…Only a few studies focused on DMSO concentrations in the North Sea because of the later evidence of the existence of particulate DMSO (DMSOp) until recent years (Simó et al, 1998) and its importance for the S cycle (Hatton et al, 2004;Green and Hatton, 2014). Unlike DMS and DMSP that are usually restricted to the euphotic zone, DMSO is ubiquitous and dominant throughout the water column (Hatton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%